2005
DOI: 10.1111/j.1600-0447.2005.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized dose‐ranging pilot trial of omega‐3 fatty acids for postpartum depression

Abstract: This study was limited by small sample size and lack of placebo group. However, these results support further study of omega-3 fatty acids as a treatment for PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 31 publications
1
128
1
2
Order By: Relevance
“…Freeman et al found decreases in diagnosed major depression (98) and diagnosed postpartum depression (99) following different doses of EPA þ DHA, Osher et al (100) found decreases in bipolar depression following supplementation with EPA, and Wozniak et al (101) found decreases in diagnosed childhood bipolar depression following supplementation with EPA þ DHA. Wozniak et al (101) also found decreases in mania and psychotic symptoms following supplementation and Sagduyu et al (102) found decreases in mania and bipolar symptoms following supplementation with EPA þ DHA.…”
Section: Trial Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Freeman et al found decreases in diagnosed major depression (98) and diagnosed postpartum depression (99) following different doses of EPA þ DHA, Osher et al (100) found decreases in bipolar depression following supplementation with EPA, and Wozniak et al (101) found decreases in diagnosed childhood bipolar depression following supplementation with EPA þ DHA. Wozniak et al (101) also found decreases in mania and psychotic symptoms following supplementation and Sagduyu et al (102) found decreases in mania and bipolar symptoms following supplementation with EPA þ DHA.…”
Section: Trial Evidencementioning
confidence: 99%
“…However, the biochemistry underlying depression, for example, may be very different to the biochemistry underlying anxiety or aggression. Similarly, DHA deficiency is thought to contribute predominantly to the development of postpartum depression (98,99) , yet DHA supplementation has not been the focus of study for other forms of depression. Differences between and within trials also exist in their definitions and measurement of outcome mood.…”
Section: Other Mood and Behavioural Disordersmentioning
confidence: 99%
“…Epidemiological studies [5,6], case-control studies [7][8][9][10][11][12] , and clinical trials [13][14][15][16][17][18] all suggest that n-3 PUFAs might play an important role in major depressive disorder (MDD). Moreover, genotypes of the key enzymes for phospholipids metabolism, such as Phospholipase A2 (PLA2) and cyclo-oxygenase-2 (COX-2), have been associated with major depressive disorder [19,20] and Interferon (IFN)-α induced depression [21].…”
Section: Introductionmentioning
confidence: 99%
“…Of the former, six were randomized controlled trials (Doornbos et al, 2009;Freeman et al, 2008;Llorent et al, 2003;Makrides et al, 2010;Mozurkewich et al, 2013;Rees, Austin, & Parker, 2008) and two pilot trials (Freeman et al, 2006;Marangell et al, 2004). The nine observational studies included: one ecological study (Hibbeln, 2002), a cross-sectional study (De Vriese, Christophe, & Maes, 2003), a case-control study (Browne, Scott, & Silvers, 2006), and six cohort studies (da Rocha & Kac, 2012;Markhus et al, 2013;Miyake et al, 2006;Otto, De Groot, & Hornstra, 2003;Parker et al, 2014;Strøm, Mortensen, Halldorsson, Thorsdottir, & Olsen, 2009).…”
Section: Overall Results In Context With Expectations Arising From Thmentioning
confidence: 99%
“…There were, however, some brief, non-systematic literature and article reviews which dealt with a broad range of issues related to our topic rather than addressing the n-3 PUFAs and PPD in particular in depth (Borja-Hart & Marino, 2010;Freeman, 2006;Levant, 2010;Jans, Giltay, & Willem Van der Does, 2010;Ramakrishnan, 2011;Wojcicki & Heyman, 2011).…”
Section: Introductionmentioning
confidence: 99%